2023
DOI: 10.1097/pcc.0000000000003167
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Extubations Requiring Reintubation in Pediatric Critical Care: An Epidemiological Study

Abstract: OBJECTIVES: Unplanned extubations are an infrequent but life-threatening adverse event in pediatric critical care. Due to the rarity of these events, previous studies have been small, limiting the generalizability of findings and the ability to detect associations. Our objectives were to describe unplanned extubations and explore predictors of unplanned extubation requiring reintubation in PICUs. DESIGN:Retrospective observational study and multilevel regression model. SETTING: PICUs participating in Virtual P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The authors found on modeling that there were two associated explanatory factors: tube-related security and (in)adequacy of patient sedation. In 2022, the journal published a United States Virtual Pediatric Systems (LLC) database study of over 5,700 unplanned extubations in 149 PICUs (2012-2020) and explored associations with the need for reintubation (10). Patients with cardiovascular disease accounted for 14% of the population, but there was no subanalysis of this group.…”
Section: What About Unplanned Extubations In Cicu Patients?mentioning
confidence: 99%
“…The authors found on modeling that there were two associated explanatory factors: tube-related security and (in)adequacy of patient sedation. In 2022, the journal published a United States Virtual Pediatric Systems (LLC) database study of over 5,700 unplanned extubations in 149 PICUs (2012-2020) and explored associations with the need for reintubation (10). Patients with cardiovascular disease accounted for 14% of the population, but there was no subanalysis of this group.…”
Section: What About Unplanned Extubations In Cicu Patients?mentioning
confidence: 99%